The transformation of the town Chomutov, its command post, fortifications and castle in the Middle Ages and the early Modern period - Sýkora, Milan (Institute of Archaeology Rzeszów University, 2012)
The article basing on archaeological, architectural and historical researches makes an attempt reconstruct the historical development of Chomutov (north east part of the Czech Republic). The author depicts the developmental history of the town starting from the 13th century colony connected with the court of the gentry, then mentioning the centre of Teutonic Knights Komtur and finally getting to the point when a town was set up nearby the monastic castle. In the middle of the 14th century a process of measuring the streets networks and parcels started. At the beginning of the 15th century Chomutov becomes a fully established city with all its lawful rights, a crest, seal, town hall and fortifications. Wacław IV has winded up the residence of Komtur in 1411 and then the city becomes a private ownership. A family of Veimitilów become the owners of the town and the castle in 1411 and they rearrange the Komtur’s center for the nobility’s residence which becomes the symbol of power over the city. The city starts to fund churches, public buildings and tenancy houses what increases its importance.
Przemiany miasta Chomutova, komendy, fortyfikacji oraz zamku w średniowieczu i na początku czasów nowożytnych
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::Archaeology subjects::Archaeology; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::Archaeology subjects::Archaeology, medieval; archaeology; history and architecture of Chomutov; architectural complex of Komtur; fortifications